Publisher Correction: A dopamine metabolite stabilizes neurotoxic amyloid-β oligomers - Rodrigo Cataldi (Nature Portfolio, 2021)
A Correction to this paper has been published: https://doi.org/10.1038/s42003-021-01680-7